Broad-scale study of the seasonal and geographic occurrence of blue and fin whales in the Southern Indian Ocean - Leroy, Emmanuelle C.; Samaran, Flore; Stafford, Kathleen M.; Bonnel, Julien; Royer, Jean-yves (Endangered Species Research, 2018)
The southern Indian Ocean is believed to be a natural territory for blue and fin whales. However, decades after commercial and illegal whaling decimated these populations, little is known about their current status, seasonal habitat or movements. Recent passive acoustic studies have described the presence of 4 acoustic populations of blue whales (Antarctic and 3 'pygmy' types), but are generally limited temporally and geographically. Here, we examine up to 7 yr of continuous acoustic recordings (2010-2016) from a hydrophone network of 6 widely spaced sites in the southern Indian Ocean, looking for the presence of Antarctic and pygmy blue and fin whales. Power spectral density analyses of characteristic and distinct frequency bands of these species show seasonal and geographic differences among the different populations, and the overall patterns for each display interannual consistencies in timing and occurrence. Antarctic blue and fin whales are recorded across the hydrophone network, mainly from austral autumn to spring, with peak intensity in winter. Pygmy blue whales show spatial variation: Madagascan pygmy blue whales are mainly present in the west of the network, while the Australian call type is heard at the eastern sites. Both populations share a common seasonality, with a presence from January to June. Finally, the Sri Lankan call type is recorded only on a single site in the northeast. These results confirm the importance of the southern Indian Ocean for several populations of endangered large whales and present the first long-term assessment of fin whales in the southern Indian Ocean.